Upaya Hukum Dalam Perkara Perdata (Verzet, Banding, Kasasi, Peninjauan Kembali dan Derden Verzet) - Syahrul Sitorus (Sekolah Tinggi Agama Islam Sumatera Medan, 2018)
Law of civil procedure (formal law) is a series of regulations which include the way how litigants act before the Court and how the Court carries out the regulation in the civil law. Legal remedy cannot be separated from formal law, either it common law or extraordinary law. In the case of civil law, especially in taking legal action, litigants should understand formal law besides material law; for example, in an appeal, cassation, and judicial review, litigants should keep time frame and carry out legal consequence on any legal remedy.